Socialization processes and family in the work of Sylvia Leser de Mello (Psicologia USP, 2006)
This paper is an attempt to describe the main axis of Sylvia Leser de Mello´s work as Social Psychology teacher, researcher of socialization processes, family and work, and as coordinator of the incubator of popular cooperative enterprises of the University of São Paulo. All of these activities were oriented by relations to students and workers that, starting from a critical scrutiny of the psychological conditions of men and women in situations of domination, are regulated by cooperation, dialogue and processes of mutual learning. In her studies and researches about socialization processes, Sylvia articulates the social scene, family life and subjectivity, resorting to the whole Human Sciences knowledge. Her work with families was consolidated in the creation of the Laboratory of Familiy, Gender Relations and Sexuality Studies of the Department of Social and Work Psychology of the Psychology Institute of the University of São Paulo which, in a transdisciplinal perspective, integrates in research, teaching and extension a group of teachers and graduation and postgraduation students from various units of the University.